Undersökning av förekomst av okända virus hos svenska fjällrävar med encefalit - Thörnvall, Helena (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2009)
The artic fox is under threat of extermination in Europe. The population decreased strongly at the beginning of the twentieth century because of intensive hunting. The artic fox was placed under protection by law 1928 in Sweden but despite this the population has had difficultly to recover. This can depend on several reasons, but the main threats are shortage of food and competition from the red fox. Along with Norway and Finland, Sweden has carried out a project called SEFALO (Saving the Endangered Fennoscandian Alopex lagopus), whose objectives were to prevent continued decreased populationnumbers and through, for example supplementary feeding, help the population to recover. 10 years ago approximately only 40 adult artic foxes were present in Sweden. Last summer, when the SEFALO-project was completed, the number was calculated to about 140 adult individuals.